Analyzing Yuji Itadori's Character Development in Jujutsu Kaisen Season 1: A Hero's Journey Approach - Firja Adica; aisah chairuna salsabila; shofi dianra zahra Damanik; Qazka Tabita Ritonga; Fikry Prastya Syahputra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the character development of Yuji Itadori in Jujutsu Kaisen Season 1 through the lens of Joseph Campbell's Hero's Journey framework. The aim is to explore how Itadori's transformation reflects contemporary themes of heroism and the moral dilemmas faced by young people today. Using a qualitative research design, the study focuses on selected episodes (1-24), employing thematic analysis to identify key moments in Itadori's journey. The findings reveal that Itadori evolves from a reluctant high school student into a determined hero, grappling with identity and responsibility. By the end of Season 1, he embodies the essence of modern heroism, emphasizing that true strength lies in protecting loved ones. This research contributes to a deeper understanding of character development in anime and highlights the relevance of traditional narrative frameworks in contemporary storytelling.